Agricultural Risk Factor Petani Lansia pada Aktivitas Pertanian Padi - Rahmawati, Novia; Farhan, Ahmad; Astuti, Pudji; Cholis S, Bambang; Azmi, Nora (Jurnal Teknik, 2023)
According to data from the Central Bureau of Statistics, the agricultural sector is the business field that absorbs the most elderly workers. However, elderly farmers actually become vulnerable to musculoskeletal disorders when doing agricultural work. This is because agriculture requires a lot of lifting activities, carrying heavy loads, working in bent and squatting positions, there is a risk of slipping and there is a risk of falling from the slippery paddy fields. This study aims to identify agricultural risks for elderly farmers. Data collection was carried out using Focus Group Discussions, to identify complaints with the Nordic Body Map (NBM) and risk assessment with the Agricultural Whole-Body Assessment (AWBA). Complaint data obtained, namely respondents stated that they had Gotrak complaints (muscle and skeletal disorders) on the waist and legs. Results questionnaire NBM, namely the level of complaints of pain in the highest part of the body that is felt, namely the waist. While the results of the AWBA risk assessment show that most of the work postures of elderly farmers are at high risk (high) with a percentage of 53% and a risk level of work duration of 73% of agricultural activities has a risk of 4 (very high).